2021
DOI: 10.1177/2050640620980203
|View full text |Cite
|
Sign up to set email alerts
|

Milan ultrasound criteria are accurate in assessing disease activity in ulcerative colitis: external validation

Abstract: Introduction The aim of this study was to provide an external validation of bowel ultrasound (US) predictors of activity in ulcerative colitis (UC) and quantitative Milan Ultrasound Criteria (MUC). Methods Forty-three consecutive patients with UC (16 in endoscopic remission and 27 with endoscopic activity) underwent bowel US and colonoscopy in a tertiary referral inflammatory bowel disease unit. Results A MUC score >6.2 discriminated patients with active versus non-active UC with a sensitivity of 0.85 (95% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
46
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(56 citation statements)
references
References 10 publications
8
46
0
2
Order By: Relevance
“…Concerning patients with UC, published studies use different cutoff values of bowel wall thickness for identifying active UC (>3 mm and 4 mm) [ 43 ]. Several IUS scores for UC have been proposed but, to date, only the Milan Ultrasound Criteria (MUC) has been validated [ 43 , 51 , 52 , 53 ]. The study for the MUC validation evaluated five initial IUS parameters, proposing a definitive score that includes bowel wall thickness and vascularization.…”
Section: Development Of Intestinal Ultrasound Scores For the Assessment Of Ibdmentioning
confidence: 99%
“…Concerning patients with UC, published studies use different cutoff values of bowel wall thickness for identifying active UC (>3 mm and 4 mm) [ 43 ]. Several IUS scores for UC have been proposed but, to date, only the Milan Ultrasound Criteria (MUC) has been validated [ 43 , 51 , 52 , 53 ]. The study for the MUC validation evaluated five initial IUS parameters, proposing a definitive score that includes bowel wall thickness and vascularization.…”
Section: Development Of Intestinal Ultrasound Scores For the Assessment Of Ibdmentioning
confidence: 99%
“…The diagnosis and the monitoring of CD is based on the combination of clinical, laboratory, and endoscopic findings; histopathological reports; and imaging studies. There are known advantages in terms of detection of BUS over endoscopy in several cases, such as an incomplete colonoscopy, proximal locations of disease (i.e., distant from the ileo-cecal valve), and complications (i.e., fistulas, abscesses, and strictures) [ 9 , 10 , 11 , 12 ]. The indications to perform BUS in CD patients are summarized in Table 2 .…”
Section: Crohn’s Disease In Bowel Ultrasoundmentioning
confidence: 99%
“…Data from comparative and prospective studies have shown a strong correlation between wall thickness (>3 and 4 mm) and colonic vascular flow with C-reactive protein values and the endoscopic score [ 9 , 10 , 41 ]. These studies have led to the full validation of an ultrasonographic score, the Milan ultrasound criteria, that can be easily calculated (1.4 × bowel thickness (mm) + 2 × vascular flow) and indicates activity when ≥6.3 [ 10 , 11 ]. In contrast with CD, in UC patients, the loss of bowel wall stratification with a hypoechoic pattern is rarely observed; when present, it is associated with a severe disease [ 45 ].…”
Section: Ulcerative Colitismentioning
confidence: 99%
See 2 more Smart Citations